Construction of the systemic anticancer immune environment in tumour-bearing humanized mouse by using liposome-encapsulated anti-programmed death ligand 1 antibody-conjugated progesterone - Kametani, Yoshie; Ito, Ryoji; Ohshima, Shino; Manabe, Yoshiyuki; Ohno, Yusuke; Shimizu, Tomoka; Yamada, Soga; Katano, Nagi; Kirigaya, Daiki; Ito, Keita; Matsumoto, Takuya; Tsuda, Banri; et al. (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors highlight the importance of anticancer immunity. However, their clinical utility and safety are limited by the low response rates and adverse effects. We focused on progesterone (P4), a hormone produced by the placenta during pregnancy, because it has multiple biological activities related to anticancer and immune regulation effects. P4 has a reversible immune regulatory function distinct from that of the stress hormone cortisol, which may drive irreversible immune suppression that promotes T cell exhaustion and apoptosis in patients with cancer. Because the anticancer effect of P4 is induced at higher than physiological concentrations, we aimed to develop a new anticancer drug by encapsulating P4 in liposomes. In this study, we showed that liposome-encapsulated anti-programmed death ligand 1 (PD-L1) antibody-conjugated P4 (Lipo-anti-PD-L1-P4) suppressed PD-L1-expressing tumor growth in vivo without toxicity. Lipo-anti-PD-L1-P4 at physiological concentrations reduced T cell exhaustion and proliferation in MDA-MB-231 cells, a triple-negative breast cancer cell line, in vitro. NOG-hIL-4-Tg mice transplanted with human peripheral blood mononuclear cells and MDA-MB-231 cells expressing PD-L1 showed suppressed tumor growth and peripheral tissue inflammation. The proportion of B cells and CD4+ T cells decreased, whereas the proportion of CD8+ T cells increased in Lipo-anti-PD-L1-P4-treated mice spleens and tumor-infiltrated lymphocytes. Our results suggested that Lipo-anti-PD-L1-P4 establishes a systemic anticancer immune environment with minimal toxicity. Thus, the use of P4 as an anticancer drug may represent a new strategy for cancer treatment.